A hybrid membrane gas absorption and bio-oxidation process for the removal of hydrogen sulfide from biogas - ÇALLI, BARIŞ (ELSEVIER SCI LTD, 2018)
A study was conducted on hydrogen sulfide (H2S) removal from biogas using a novel hybrid polydimethylsiloxane (PDMS) membrane bioscrubber. The effect of absorption liquid pH, biogas flowrate and DO concentration on H2S selectivity, removal efficiency and sulfide oxidation were investigated. The process performance at pH 7 was better than pH 8.5 in terms of H2S removal capacity and selectivity. Desulfurization selectivity of H2S/CO2 and H2S/CH4 increased along with the increase of gas flowrate (32 l/d) and reached 3.5 and 63, respectively. The calorific value of the biogas significantly increased due to the raising of CH4 content by 21%. During the long-term operation, air diffusion through the membrane into the biogas was not observed. Almost complete H2S removal (> 97%) and high conversion ratio to S (> 74%) were achieved when volumetric loading rate and DO concentration were kept below 148 g H2S/m(3)d and 1 mg/l, respectively. Partial oxidation of sulfide to S (1 mg/l) rather than sulfate (4 mg/l) reduced the caustic consumption by half. Even though S and inorganics were detected on membrane surface with SEM-EDS analysis, fouling and wetting problems were not observed. The novel hybrid process developed in this study is a cost-effective and robust alternative to conventional biogas desulfurization.
Keywords: Biogas; Desulfurization selectivity; Membrane bioscrubber; Sulfide oxidation; ANAEROBIC-DIGESTION; H2S; OXIDATION; DESULFURIZATION; CO2; TECHNOLOGIES; PERFORMANCE; STRATEGIES; EMISSION; MIXTURE